Research and development activities in Belgium: A snapshot of past investment for the country's future - Saskia Vennix (National Bank of Belgium, 2019)
Recent changes in the accounting legislation regarding the accounting and disclosure of research and development (R&D) expenditure in the financial statements have triggered this research on the importance of this kind of activities and their impact at microeconomic level. Using survey data, a solid sample of 1,964 R&D companies was compiled. Based on this sample, some of the main characteristics of R&D firms are presented, such as sector of activity, age, geographic location, etc. In 2016, these 1,964 R&D entities together employed nearly 279,000 people and generated exteuro 45 billion of value added, which represents 6 % of Belgium's domestic employment and 10.6 % of the country's gross domestic product. By means of statistical techniques, the microeconomic impact of R&D efforts on average annual growth of value added, average annual employment growth and average annual growth of labour productivity is investigated. Following this research, the conclusion is that R&D investment has generally had a positive impact on average annual growth of value added and average annual employment growth for periods of four years or longer. In a shorter timespan (less than four years), such a positive impact of R&D involvement could not be demonstrated. For the average annual growth of labour productivity, no evidence of any difference between the R&D and the non-R&D group was found.
Keywords: D22; J21; L25; O33; 330; microeconomic data; corporate R&D; firm performance; employment; value added; Belgian firms